Life after trafficking: reintegration experiences of human trafficking survivors in Nigeria. Issue 4 (13th September 2021) - Idemudia, Uwafiokun; Okoli, Nnenna; Goitom, Mary; Bawa, Sylvia
Abstract : Purpose: Reintegration programs have emerged as part of the regimes of care for survivors of human trafficking. However, empirical analysis of the reintegration outcomes for survivors remains limited in the African context. Hence, this paper aims to examine the challenges and opportunities of reintegration assistance programs for survivors of human trafficking in Nigeria. Design/methodology/approach: Drawing on qualitative methods of data collection and analysis, this study conducted semi-structured interviews with repatriated women who have accessed reintegration assistance in Nigeria, and data was analyzed using thematic analysis. Findings: The findings suggest that while the reintegration programs might address the procedural aspect of reintegration, the achievement of substantive reintegration remains incomplete. This is because of the structural conditions of the context within which reintegration is supposed to occur. Practical implications: There is a need to take seriously the distinction between the reintegration of survivors into a new community or a former community in the design of a regime of care for survivors of human trafficking in Africa. Crucially, the focus on procedural reintegration should not also divert attention away from the structural conditions and reforms needed to ensure survivors achieve substantive reintegration. Originality/value: This paper contributes to the limited literature on life after trafficking and demonstrates the strengths and limitations of reintegration programs as a regime of care for survivors of human trafficking. In addition, this study empirically grounded the theoretical distinction between different aspects of the process of reintegration.